2007
DOI: 10.1159/000100106
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aldosterone in Left Ventricular Hypertrophy among African-American Patients with End-Stage Renal Disease on Hemodialysis

Abstract: Aims: Recently, serum aldosterone levels have been reported to play a significant role in cardiac hypertrophy. One study of Japanese patients correlated aldosterone levels with the degree of left ventricular hypertrophy (LVH) in those undergoing hemodialysis. However, the role of aldosterone in LVH in non-Japanese patients with end-stage renal disease (ESRD) has not been established. Materials and Methods: Researchers evaluated 42 [29 African-Americans (69%), 11 Caucasians (26%), and 2 other (5%)] male ESRD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
1
23
1
3
Order By: Relevance
“…24 Persistent hyperaldosteronemia and/or activation of MR can promote cardiac fibrosis, possibly through generation of signals promoting profibrotic TGF-b production. 1,25,26 In animal models, spironolactone ameliorates cardiac fibrosis in nephrectomized uremic rats. 27,28 We evaluated the effects of adding spironolactone to ACEI or ARB in patients undergoing PD, and we found that LVMI was significantly suppressed in the spironolactone group (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…24 Persistent hyperaldosteronemia and/or activation of MR can promote cardiac fibrosis, possibly through generation of signals promoting profibrotic TGF-b production. 1,25,26 In animal models, spironolactone ameliorates cardiac fibrosis in nephrectomized uremic rats. 27,28 We evaluated the effects of adding spironolactone to ACEI or ARB in patients undergoing PD, and we found that LVMI was significantly suppressed in the spironolactone group (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The ones in the first category are represented by an increase in systemic arterial resistance, elevated arterial blood pressure, and reduced large-vessel compliance [17,18,19,20] related in part to aortic ‘calcification', which is typical in CKD patients; all these factors result in myocardial cell thickening and concentric LV remodeling often together with activation of the intracardiac renin-angiotensin system [19,21]. …”
Section: Pathophysiology Of Lvh In Ckd Patientsmentioning
confidence: 99%
“…These afterload-related factors result in myocardial cell thickening and concentric LV remodeling. Activation of the intracardiac renin-angiotensin system (RAS) seems to be critically involved in this pathway, but angiotensin II and aldosterone as well can also be involved in myocardial cell hypertrophy and fibrosis, independent of afterload (23,25,26). Non-angiotensin II-dependent pathways for induction of LVH by mechanical stretch have been identified (27).…”
Section: What Are the Likely Pathophysiologic And Pathobiologic Mechamentioning
confidence: 99%
“…Persistent hyperaldosteronemia, consequent to activation of RAS or through non-RAS-dependent factors, can promote cardiac fibrosis, perhaps through generation of signals promoting profibrotic transforming growth factor ␤ production (23,26). Deficiency states, such as iron and/or erythropoietin (with attendant anemia), and perhaps carnitine deficiency as well can promote LVH (49).…”
Section: What Are the Likely Pathophysiologic And Pathobiologic Mechamentioning
confidence: 99%